The Effect of Pet Attachment, Self-Compassion, and Social Constraint on Pet Bereavement - Wulandari, Shannen Septyanti; Wahyuni, Zulfa Indira (TAZKIYA Journal of Psychology, 2025)
Pets play a significant role in their owners' lives. Psychological studies have found that pet loss is one of the contributing factors to depression. The grieving response experienced by pet owners following the loss of their pets is referred to as pet bereavement. This study aims to examine the influence of pet attachment, self-compassion, and social constraint on pet bereavement. This research employs a quantitative approach with a sample of 250 individuals who have experienced pet loss and reside in Indonesia. The sampling technique used is non-probability sampling. The Pet Bereavement Questionnaire (PBQ) developed by Hunt & Padilla (2006) was used to measure pet bereavement, the Lexington Attachment to Pet Scale (LAPS) developed by Johnson et al. (1992) was used to assess pet attachment. Self-compassion was measured using the Self-Compassion Scale (SCS) developed by Neff (2003), and social constraint was assessed using the Social Constraint Scale developed by Lepore et al. (1996). Data analysis was conducted using multiple regression analysis. The regression test results showed an R-squared value of .727, indicating that pet attachment, self-compassion, and social constraint significantly influence pet bereavement, accounting for 72.7% of the variance. The significance test results revealed that three variables had a significant impact on pet bereavement: general attachment (p < .05), people substituting (p < .05), and gender (p < .05). Based on these findings, it is recommended that pet owners develop a healthy attachment to their pets and engage with animal lover communities to receive social support during times of loss.